The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3991/ijim.v16i02.27307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using ‘Microb’ Mobile Application in Science Learning in Primary School

Abstract: The study investigated the relationship between the overall scientific performance of the pre-test and post-test and the impact of the application of "Microb" on scientific performance. The theme is "microorganisms and their effects". The sample group consisted of 30. Year 5 pupils’ from a primary school in Johor Bahru. They were selected for this quantitative study through purposeful sampling. Investigation, pre-test and post-test are used to collect research data. The results show that based on the four scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The use of smart applications in various purposes is a current trend, the ease and effectiveness of this application is the main purpose of its use. Research on the use of smart applications can be found in various purposes such as youth financial management [31], science learning in primary school [32], disseminating messages and events of university colleges [33], and the formation of analytical competence of future specialists [34], including in the field of sports education [35]. The use of smart applications in sports education, such as the smart application in swimming, is interesting to discuss, because the use of smart applications in learning to swim is something that can give students interest and interest in learning to swim.…”
Section: Multicollinearity Testmentioning
confidence: 99%
“…The use of smart applications in various purposes is a current trend, the ease and effectiveness of this application is the main purpose of its use. Research on the use of smart applications can be found in various purposes such as youth financial management [31], science learning in primary school [32], disseminating messages and events of university colleges [33], and the formation of analytical competence of future specialists [34], including in the field of sports education [35]. The use of smart applications in sports education, such as the smart application in swimming, is interesting to discuss, because the use of smart applications in learning to swim is something that can give students interest and interest in learning to swim.…”
Section: Multicollinearity Testmentioning
confidence: 99%
“…The Woods model offers a structured approach to science learning that actively involves students in making predictions, conducting observations, and constructing explanations based on evidence [33]. It aims to foster conceptual change and enhance students' understanding of scientific concepts by building on their prior knowledge and promoting active engagement in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“… Good human-computer interaction (HCI) relations among students in Turkey [63].  Understanding skills, scientific processes, and applying scientific reasoning skills [64].  Easy, convenient, practical, and accessible anywhere to students in Malaysia [65].…”
Section: Introductionmentioning
confidence: 99%